2009
DOI: 10.1021/np900354q
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Lactones from the Root Tubers of Lindera aggregata

Abstract: Phytochemical investigation of the root tubers of Lindera aggregata resulted in the isolation of five new sesquiterpene lactones, linderagalactones A-E (1-5), along with eight known sesquiterpenoids, 3-eudesmene-1beta,11-diol, hydroxylindestenolide, strychnistenolide, hydroxyisogermafurenolide, atractylenolide III, linderane, neolinderalactone, and linderalactone. The structures and relative configurations of 1-5 were determined by spectroscopic methods, especially HRESIMS and 2D NMR techniques. The absolute c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 28 publications
1
56
0
Order By: Relevance
“…Our findings were in line with previous reports. Gan et al (2009) reported that linderagalactone E (5), linderane, hydroxylindestenolide, and linderalactone showed hepatoprotective activity against H 2 O 2 -induced oxidative damages on HepG2 cells. In addition, huperzine A showed protective activity against H 2 O 2 -induced damage in SHSY5Y cells (Tang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings were in line with previous reports. Gan et al (2009) reported that linderagalactone E (5), linderane, hydroxylindestenolide, and linderalactone showed hepatoprotective activity against H 2 O 2 -induced oxidative damages on HepG2 cells. In addition, huperzine A showed protective activity against H 2 O 2 -induced damage in SHSY5Y cells (Tang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…They have long been investigated for biological activities; anticarcinogenic (Afoulous et al 2013), antimicrobial (Wang et al 2013), antifungal (Kundu et al 2013), antiinflammatory (Wang et al 2013), more recently, and antioxidant activities (Abolaji et al 2013). Also it was reported that sesquiterpenes could provide protection against H 2 O 2 damage in many cell lines (Tang et al 2005;Umemura et al 2008;Gan et al 2009;Turkez et al 2013). Cyclosativene (CSV) is a tetracyclic sesquiterpene (Fig.…”
mentioning
confidence: 99%
“…It has been used to treat chest and abdominal pain, indigestion, regurgitation, colds, hernia and frequent urination (22). Studies have demonstrated that L. aggregata extract has antioxidant properties, and can inhibit tumor cell growth and induce apoptosis (23)(24)(25)(26) (27) verified that ILL could induce apoptosis in the human breast cancer MDA-MB-231 cell line, possibly via the inhibition of microRNA hsa-miR-30c expression and increasing the expression of suppressor of cytokine signaling 3 (SOCS3). This in turn inhibits the phosphorylation of signal transducer and activator of transcription 3 (STAT3) and regulates the downstream processing of STAT3 pathways, increasing B-cell lymphoma-2 (Bcl-2) and Bcl-extra large protein expression, and inhibiting X-linked inhibitor of apoptosis expression.…”
Section: Introductionmentioning
confidence: 99%
“…In China, it is known as Wu Yao and in Japan, Uyaku. Lauraceae is used for treating renal, cystic and rheumatic diseases (9). Lindera aggregata, isolinderalactone, linderalactone and linderane are known sesquiterpenes derived from root tubers.…”
Section: Introductionmentioning
confidence: 99%